Fisheries management influences phytoplankton biomass of Amazonian floodplain lakes - Campos-Silva, Joaõ Vitor; Peres, Carlos A.; Amaral, João Henrique Fernandes; Sarmento, Hugo; Forsberg, Bruce Rider; Fonseca, Carlos Roberto (Journal of Applied Ecology, 2020)
Tropical floodplains secure the protein supply of millions of people, but only sound management can ensure the long-term continuity of such ecosystem services. Overfishing is a widespread threat to multitrophic systems, but how it affects ecosystem functioning is poorly understood, particularly in tropical freshwater food webs. Models based on temperate lakes frequently assume that primary producers are mostly bottom-up controlled by nutrient and light limitations, with negligible effects of top-down forces. Yet this assumption remains untested in complex tropical freshwater systems experiencing marked spatiotemporal variation. We use consolidated community-based fisheries management practices and spatial zoning to test the relative importance of bottom-up versus top-down drivers of phytoplankton biomass, controlling for the influence of local to landscape heterogeneity. Our study focuses on 58 large Amazonian floodplain lakes under different management regimes that resulted in a gradient of apex-predator abundance. These lakes, distributed along ~600 km of a major tributary of the Amazon River, varied widely in size, structure, landscape context, and hydrological seasonality. Using generalised linear models, we show that community-based fisheries management, which controls the density of apex predators, is the strongest predictor of phytoplankton biomass during the dry season, when lakes become discrete landscape units. Water transparency also emerges as an important bottom-up factor, but phosphorus, nitrogen and several lake and landscape metrics had minor or no effects on phytoplankton biomass. During the wet-season food pulse, when lakes become connected to adjacent water bodies and homogenise the landscape, only lake depth explained phytoplankton biomass. Synthesis and applications. Tropical freshwaters fisheries typically assume that fish biomass is controlled by bottom-up mechanisms, so that overexploitation of large predators would not affect overall ecosystem productivity. Our results, however, show that top-down forces are important drivers of primary productivity in tropical lakes, above and beyond the effects of bottom-up factors. This helps us to understand the enormous success of community-based ‘fishing agreements’ in the Amazon. Multiple stakeholders should embrace socio-ecological management practices that shape both bottom-up and top-down forces to ensure biodiversity protection, sustainable fisheries yields and food security for local communities and regional economies. © 2020 The Authors. Journal of Applied Ecology published by John Wiley & Sons Ltd on behalf of British Ecological Society
Keywords: community-based management; Flood Pulse; Food Security; Freshwater Ecosystem; lake ecology; Limnology; Primary Production; Trophic Cascade